Empowering Nonprofits: The Role of Sustainable Spiritual Leadership in Driving Performance - Kristanto, Agus Budi; Ekawati, Erni (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
This study investigates the impact of sustainable spiritual leadership on the performance of nonprofit organizations, specifically focusing on 64 churches within the East Java Christian Church (GKJW) Synod from 2021 to 2023. The research uses quantitative data and a multiple regression model to assess spiritual leadership across three dimensions: Pastoral Ministry, Church Ministry, and Leadership. The findings reveal that Church Ministry has a positive and significant effect on organizational performance, while Pastoral Ministry and Leadership have negative yet significant impacts. These results suggest that improving Pastoral Ministry and Leadership may temporarily reduce performance but is essential for fostering long-term sustainable spiritual leadership. On the other hand, Church Ministry produces immediate performance benefits. The study emphasizes the complexity of promoting sustainable spiritual leadership, as all three dimensions need to be harmonized for long-term organizational success and societal impact. The research offers empirical evidence, highlighting the need for balancing short-term performance outcomes with the development of sustainable leadership practices in nonprofit organizations.